Assessing the impact of disabilities on healthcare access among Sudanese refugees in Egypt during the 2023 crisis: a discriminant analysis approach - Semary, Hatem E.; Abdel-Rahman, Suzan; Al-Karawi, Khamis A.; Abdelwahab, Mahmoud M.; Dossouvi, Komla Mawunyo; Elkelish, Amr; El Shabrawy, Abdelhamid (Frontiers in Medicine, 2025)
IntroductionThe longstanding presence of Sudanese refugees in Egypt—fueled by decades of political instability, conflict, and economic hardship in Sudan—has evolved with the recent 2023 crisis. This study investigates the living conditions, health status, and the impact of disabilities on healthcare access among newly displaced Sudanese in Egypt.MethodsA phone-based survey was administered to 531 Sudanese refugees. Descriptive statistics were first used to summarize the key demographic and household characteristics of the sample. The data was then analyzed using discriminant analysis to distinguish between families with and without healthcare challenges.ResultsThe sample had a mean age of 39.85 years, and the majority were female (75.5%), married (61.4%), and possessed a university-level education or higher (50.5%). On average, 4.92 family members migrated to Egypt with the respondent. The analysis revealed that chronic conditions such as spinal diseases and diabetes, along with the need for regular monthly treatment, were the strongest predictors of healthcare challenges among Sudanese refugee families. Additionally, disabilities including vision impairments, mobility difficulties, and intellectual disabilities were significantly associated with increased barriers to accessing healthcare services.DiscussionThese findings underscore the compounded vulnerabilities of Sudanese refugees with disabilities and highlight the urgent need for targeted interventions to enhance healthcare accessibility and overall wellbeing. The results further stress the need for disability-sensitive health responses during refugee crises.